Health Indicators of US Older Adults Who Received or Did Not Receive Meals Funded by the Older Americans Act - Edgar R. Vieira; Joan A. Vaccaro; Gustavo G. Zarini; Fatma G. Huffman (Journal of Aging Research)
Background. The Older Americans Act (OAA) requires that nutrition programs provide meals and related nutrition services that promote health and help manage chronic diseases. The purpose of this study was to compare health status, food security, functional limitations, and chronic diseases of older adults who received or did not receive OAA meals using data from a representative sample of US adults. Methods. Data were from the National Health and Nutrition Surveys 2011–2014 for 2,392 older adults ≥ 65 years of age, including 187 Mexican Americans, 212 other Hispanics, 521 non-Hispanic Blacks, 219 non-Hispanic Asians, and 1253 non-Hispanic Whites. Results. Those receiving OAA meals had higher percent of food insecurity and functional disabilities. Adjusting for potential confounders, adults who received OAA meals had higher odds of emphysema (OR = 2.02; 1.05, 3.89) and lower odds of good-to-excellent health (OR = 0.52; 0.36, 0.77). Women and minorities had poorer health status compared to non-Hispanic Whites. Conclusion. A higher proportion of older adults who received nutritional services reported poorer health as compared to older adults who do not participate in these services. Future studies should assess nutritional adequacy for older adults who participate in nutritional programs comparing sex and race/ethnicity.